Snakes - Gross, Ruth Belov (New York : Scholastic, 1973)
Describes the habits and behavior of some common snakes that are found chiefly in the United States and Canada, including four poisonous kinds.
School Library Journal
Publishers Weekly
Kirkus Reviews
4.3
K-3
Keywords: Snakes -- Juvenile literature; Snakes; Snakes